Strategies to inculcate moral values in Islamic Elementary School - Nurhayati, Riana (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
This study aims to explore the integration of moral values into learning activities, management, and student guidance activities. This study employed a descriptive qualitative approach. The data were collected through three techniques, namely in-depth interviews, participant observations, and a document study. The research respondents were principals, teachers, and students until the data was saturated. The sampling technique used was simple random sampling. For data analysis, Miles and Huberman's method of interactive qualitative analysis was used, which consists of data condensation, data display, and conclusion/verifying. The data trustworthiness was enhanced through conti-nuous observations and resource and technique triangulations. The results of the study show that the strategy of inculcating moral values at Islamic elementary school can have a positive impact on the moral values of its students. Moral values can be integrated into learning activities through the strategies of reward and punishment, storytelling, spontaneous or direct activities, the setting of good examples and habits, and readings from the Al Qur'an. Moral values can be integrated into management through the strategies of Al Qur'an recitation, tahfidh or the memorization of the short surah, alma'surat, collective dhuhur (noon) and Friday prayers, and organized lunches with dhuha prayers. Moral values may be integrated into student guidance activities on market days, through scouting and other outbound activities, and through mabit, muhayyam, and gardening.